2020
DOI: 10.1038/s41419-020-03146-w
|View full text |Cite
|
Sign up to set email alerts
|

GDC-0349 inhibits non-small cell lung cancer cell growth

Abstract: Non-small cell lung cancer (NSCLC) is a leading cause of cancer-related human mortality with a clear need for new therapeutic intervention. GDC-0349 is a potent and selective ATP-competitive mTOR inhibitor. In A549 cells and primary human NSCLC cells, GDC-0349 inhibited cell growth, proliferation, cell cycle progression, migration and invasion, while inducing significant apoptosis activation. Although GDC-0349 blocked Akt-mTORC1/2 activation in NSCLC cells, it also exerted cytotoxicity in Akt1-knockout A549 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…It is also associated with apoptosis inhibition and therapy-resistance, and represents as an important therapeutic target of NSCLC [ 5 , 38 41 ]. Targeted inhibition of mTOR cascade, on the other hand, could produce significant anti-tumor activity in NSCLC cells [ 29 , 38 , 41 , 42 ]. Bonekamp et al found that POLRMT inhibition by small molecular inhibitors could result in robust inhibition of S6 phosphorylation [ 15 ], a key indicator of mTORC1 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also associated with apoptosis inhibition and therapy-resistance, and represents as an important therapeutic target of NSCLC [ 5 , 38 41 ]. Targeted inhibition of mTOR cascade, on the other hand, could produce significant anti-tumor activity in NSCLC cells [ 29 , 38 , 41 , 42 ]. Bonekamp et al found that POLRMT inhibition by small molecular inhibitors could result in robust inhibition of S6 phosphorylation [ 15 ], a key indicator of mTORC1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…A549 cell line was from Dr Li at Wenzhou Medical University [ 28 , 29 ] and cells was cultivated in RPMI-1640 medium containing 8% FBS in a humidified atmosphere containing 5% CO 2 . Using the described protocols [ 30 , 31 ], the primary human NSCLC cells were derived from three different patients, pNSCLC1, pNSCLC2, and pNSCLC3.…”
Section: Methodsmentioning
confidence: 99%
“…mTOR acts in a synergistic manner to inhibit tumor growth in mouse prostate and lung cancer models, and phosphorylated or activated mTOR is found in 74% of the NSCLCs, making it an additional target for NSCLC therapy ( Marinov et al, 2007 ). In A549 and primary human NSCLC cells, GDC-0349 inhibits NSCLC cell growth, proliferation, cell cycle progression, migration, and invasion through the Akt-Akt-mTOR pathway, while inducing significant apoptotic activation ( Yang et al, 2020 ). Analysis of a receiver operating characteristic curve (area under curve = 0.6785) showed that the expression of MCL-1 is an important critical value for predicting prognosis in 30.0% of the NSCLC tumor cell types.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant adenoviral construct encoding the constitutively-active Akt1 (caAkt1, S473D) was provided by Dr. Li at Wenzhou Medical University ( 26 , 27 ), and was transduced to pNSCLC-1 cells. Cells with GFP were then sorted by FACS and monoclonal single cells were distributed into 192-well plates.…”
Section: Methodsmentioning
confidence: 99%